2016
DOI: 10.1051/0004-6361/201527281
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of Pluto, 0.40–0.93μm

Abstract: Context. During the past 30 years the surface of Pluto has been characterized and its variability monitored through continuous nearinfrared spectroscopic observations. But in the visible range only a few data are available. Aims. The aim of this work is to define Pluto's relative reflectance in the visible range to characterize the different components of its surface, and to provide ground based observations in support of the New Horizons mission. Methods. We observed Pluto on six nights between May and July 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…Also, alkanes were suggested to contribute to certain features in Plutoʼs spectra by studying several linear and branched alkanes diluted in nitrogen ice (Bohn et al 1994). Recently, Lorenzi et al (2016) suggested that the discoloration of Pluto along with Makemake and Eris may be due to COMs, and our present study shows that this is very likely just from the simple ethane ice. Dangi et al (2015) has shown that under model atmospheric conditions containing C3 and C4, hydrocarbons interact catalytically with surfaces of micrometeroids to produce a carbonaceous refractory layer, which can account for the hydrocarbon sequestration.…”
Section: Astrophysical Implicationssupporting
confidence: 56%
“…Also, alkanes were suggested to contribute to certain features in Plutoʼs spectra by studying several linear and branched alkanes diluted in nitrogen ice (Bohn et al 1994). Recently, Lorenzi et al (2016) suggested that the discoloration of Pluto along with Makemake and Eris may be due to COMs, and our present study shows that this is very likely just from the simple ethane ice. Dangi et al (2015) has shown that under model atmospheric conditions containing C3 and C4, hydrocarbons interact catalytically with surfaces of micrometeroids to produce a carbonaceous refractory layer, which can account for the hydrocarbon sequestration.…”
Section: Astrophysical Implicationssupporting
confidence: 56%
“…We did not establish reference magnitude for Pluto in this paper and a search of the literature did not locate values for R C and I C . Therefore we synthesized magnitudes from the spectral profile shown in Figure 3 of Lorenzi et al (2016). Since their data are given as a relative reflectance value rather than in absolute energy units, we adjusted our synthetic magnitudes such that the albedo corresponding to our V value agreed with the average albedo cited in their Table 1.…”
Section: Applications To Exo-planetsmentioning
confidence: 99%
“…The spectral slope measured for Makemake is S M = (21.2 ± 0.6) %/1000 Å and for Eris is S E = (13.5 ± 0.2) %/1000 Å. Notice that these values are not to be directly compared with others in the literature (for instance Lorenzi et al 2016) because these values are dependent of the exact definition used for S , which changes from work to work.…”
Section: Spectrum In the Visiblementioning
confidence: 97%

The Dwarf Planet Makemake as seen by X-Shooter

Alvarez-Candal,
Souza-Feliciano,
Martins-Filho
et al. 2020
Preprint
Self Cite